PENGARUH KENAIKAN NILAI JUAL OBJEK PAJAK (NJOP) DAN UNDANG-UNDANG HUBUNGAN KEUANGAN ANTARA PEMERINTAH PUSAT DAN DAERAH (UU HKPD) TERHADAP REALISASI PENERIMAAN PAJAK BUMI DAN BANGUNAN - Hartono, Nicky Dwi; Nugroho, Gatot Wahyu; Tanjung, Hendra (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine and explain the effect of the increase in the selling value of tax objects (NJOP) and the Law on Financial Relations between the Central and Regional Governments (HKPD Law) on the Realization of Land and Building Tax Revenue. This study uses a Quantitative Method with an associative approach that collects data through distributing questionnaires. The population in this study were PBB-P2 taxpayers in Sukabumi City. The sample was taken using nonprobability sampling technique, which does not provide equal opportunities for each element of the population to be selected as a sample and determined through the slovin formula, namely 101 taxpayers. The results of hypothesis testing from the t test of variable X1 show that the value of t count> t table is 2.458> 1.984 where from these results it is concluded that the variable NJOP increase has a positive and significant effect on the realization of PBB revenue, then the first hypothesis is accepted. The results of the t test of variable X2 show that the value of t count > t table with a number 6.510 > 1.984 and it is concluded that the HKPD Act variable has a positive and significant effect on the realization of PBB revenue, so the second hypothesis is accepted. The results of the F test show that the value of f count > f table with a number of 28.203 > 3.090 with a significance of <0.001 <0.05 which means that the third hypothesis is accepted. So from the results it is concluded that the independent variables simultaneously have a positive and significant effect on the realization of PBB revenue. The result of the coefficient of determination test of variable Y is 35% with the remaining 65% influenced by other variables not listed in this study. Thus it can be concluded that the increase in NJOP and the HKPD Law has a positive and significant effect on the Realization of Rural and Urban Land and Building Tax Revenue in Sukabumi City.